O Museu Afrodigital do Maranhão como dispositivo democratizante e educativo - NOGUEIRA, Juliana dos Santos (2018)
The constant technological changes and the dynamism of information make society have the need to adapt faster and faster to a new scenario. This process includes the most diverse sectors and institutions, including museums and education. In this sense, based on an action research, it is sought to reflect on the role of the Afrodigital Museum of Maranhão in expanding the possibilities of dissemination of knowledge with the objective of developing discussions about proposals for the construction of cultural and informational democratization of this technology, also of the use of the site as a teaching and learning device understanding how this process is developed. Thus, this research was based on the following steps: Analysis of the site as a teaching tool, meetings with MADMA team to discuss the project The Afro Digital Museum of UFMA as a methodological tool: an experience in public high schools of the Maranhão, alignment and application of the tool in three high schools of the public school of São Luís, analysis and discussion of the results and finally the dissemination of the experience. It should be pointed out that the research results pointed to the strong potential of museum education focused, above all, to fill gaps left by formal education, pointed out the importance of Social Networks in the educational process in virtual environments, especially Facebook, among In addition, the results also emphasized the constant need for museum adaptation to a decolonial perspective that displaced Afro-descendant peoples from objects to subjects of discussion, with a central role in the process.